Predictors and outcomes of cyberbullying among college students: A two wave study. Issue 1 (26th August 2021) - Giumetti, Gary W.; Kowalski, Robin M.; Feinn, Richard S.
Abstract: Existing research on cyberbullying has primarily focused on adolescents in cross‐sectional survey studies, with less research focusing on college students or employed adults over longer periods of time. To extend this literature, the current study examined new predictors and outcomes of cyberbullying perpetration (CP) and victimization (CV) among college students from two different universities that were followed across two time points. Risk factors were measured in line with previous theoretical models, including biological or personality‐related variables (e.g., low self‐control, dark‐side personality traits, empathy) and environmental variables (e.g., perceived social support, lack of rule clarity, and internet use). Additionally, we examined several possible outcomes of CV and CP. Results from path analyses revealed that involvement with traditional bullying (either as a perpetrator or a victim) as well as Machiavellianism significantly predicted CV and CP. With regard to the cross‐lagged associations between CV and CP, we found that Time 1 CV predicted time 2 CP, but Time 1 CP did not predict Time 2 CV. That is, being a victim of cyberbullying during the Fall semester predicted involvement as a perpetrator in the Spring semester. However, being a perpetrator during the Fall semester did not predict being a victim during the Spring semester. Regarding outcomes, we found that CV significantly predicted anxiety, depression, and helping behavior, and CP significantly predicted deviant behavior, but not GPA nor alcohol consumption. These findings have practical implications for college students as well as university student support services.